CONSTRUCTION AND PRACTICAL APPLICATION OF A CANOPY OPENER DEVICE - Prado, Evandro P. [UNESP]; Dal Pogetto, Mario H. F. Do A.; De Cerqueira, Denise T. R.; Raetano, Carlos G. [UNESP]; Costa, Saulo I. De A. [UNESP] (Soc Brasil Engenharia Agricola, 2016)
Accurate application of pesticides is difficult for crops with dense leaves, such as soybean crops. To improve spray deposits on the lower leaves of soybean plants, the aim of this study is to build a canopy opener (CO) from a previously developed prototype and to assess its practical application and efficiency on soybean crops. Laboratory experiments were conducted to determine the amount of spray deposits on the top and the lower leaves using a Brilliant Blue dye. The influence of the CO device on the number of flowers knocked down during spraying was also investigated. The data showed that the use of the CO attached to the spray boom enabled more spray deposits on the lower leaves and less spray deposits on the upper leaves compared with conventional spraying. The CO device did not influence the falling of flowers or the damage to the soybean plants. The construction of the CO device proved to be a feasible alternative, which could be used primarily by small-scale soybean producers, with the goal of obtaining larger spray deposits on the lower leaves of soybean plants.
Keywords: Application technology; soybean; spray deposit